As representações de memórias sobre a loucura e a escrita autobiográfica na narrativa de Hospício é Deus, de Maura Lopes Cançado - Marangon, Vinícius (2024)
This master thesis takes place among those studies that, in the current scenario of comparative literature approaches in Latin America, tend to include literary manifestations that were ignored by past literariness criteria aligned with an ethnocentric orientation (Carvalhal, 2003, 2006; Coutinho, 2010). Among those manifestations, the ones that report to social groups that were targeted with exclusion processes stand out, which is the case of those individuals labeled as mad or mentally ill. Hospício é deus (1968/2021), a novel by the Brazilian writer Maura Lopes Cançado and the object of this study, reports on a social frame in which power regulates the discourses about the experience of madness. By representing her memories from the intimate point of view of a person admitted to a mental institution, Maura's narrative establishes important dialogues with the official history about the processes through which madness was recommended, for a long time, to be hospitalized. Thus, the general objective of this master thesis is to investigate how the memories represented in Hospício é deus are configured and what function they assume, seeking to identify the biographical values with which such representations invest the work of Maura Lopes Cançado. To this end, we define the following as specific objectives: Review the contributions of relevant authors to build an interdisciplinary theoretical apparatus on the theme of madness and biographical narratives; Carry out a critical reading of Hospício é deus; Investigate how the memories present in the narrative are configured, and what functions they assume; Investigate which stigmas are associated with the figures of the mad or mentally ill individuals, and other central characters in the reported memories; Reflect, with an interdisciplinary and contrastive perspective, on the influence that social, historical and cultural dimensions have on the way in which memories are taken up by the narrative selected for study. To do that, this work is composed of three sections, excluding the final considerations, intended, respectively, for the introduction, the theoretical framework, and the critical reading of Hospício é deus. In the theoretical framework, we fulfilled the first specific objective mentioned above by returning to the thoughts of authors such as Foucault (2002a, 2006, 2009, 2019), Goffman (2008), Jodelet (2001), Halbwachs (1990), Ricoeur (2007) and Arfuch (2010) to establish important concepts that guided the posterior reading. In the third section, intended for the critical reading of the novel, the concept of ―biographical value‖, as understood by Arfuch (2010), was taken as an analytical vector that allows a transversal reading of the narratives that, like Hospício é deus, share the biographical space. Guided by that vector and in dialogue with the social, cultural, and historical framework that we recovered in the theoretical framework, our reading of Hospício é deus sheds light on an ethical dimension that organizes the selection of memories and experiences by the narrator-protagonist, which establishes relationships with social issues much broader than the singularity of the narrated memories.